David Sassoon Clock Tower - Ghosh, Ayan (2023)
The David Sassoon clock tower originally stood outside the gates of Victoria Garden, by the side of the main road, then known as Parel Road (now BR Ambedkar Road). In 1926, during road widening, the clock tower was dismantled brick by brick and reconstructed at its present location. The shifting was done with great sensitivity and care, retaining the earlier alignment.